Analisis Kepuasan Sistem Informasi Desa Sidomoro di Kabupaten Kebumen Menggunakan Metode End User Computing Satisfaction - Muhamad Hamzah Baqi; Resad Setyadi; M. Eka Purbaya (JURIKOM (Jurnal Riset Komputer), 2022)
Currently, technology has become a fast and easy access to information data. Technology contributes to the arrangement of management systems and processes in both government and private institutions. Utilization of Information Technology (IT) is mandatory in today's modern era. One of the applications of IT in village life is the use of the Village Information System (SID). SID provides benefits to the community in terms of information related to the village, namely in terms of the shape of the area, population, tourist attractions and correspondence services. Preliminary observations of the study indicate that the use of SID in Sidomoro Village still has performance deficiencies, namely service constraints, the lack of functioning of several features in Sidomoro SID, system loading problems and system accuracy from Sidomoro SID. This constraint affects user service satisfaction in Sidomoro village. This study requires testing the number of respondents from the village apparatus and the Sidomoro village community. The user satisfaction test model in this study was successful in analyzing the EUCS model. The results of the question analysis show that this research has a valid and reliable value. The satisfaction value of using the SIDOMORO village SID is 64.79. The value above 65% means that the Sidomoro people are satisfied with using SID in 2020-2021. The recommendation of this research is that the Sidomoro Village SID requires improvements to the loading section and system accuracy through periodic planning to achieve a very satisfactory level.